2014
DOI: 10.2527/jas.2013-7318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary zinc and ractopamine hydrochloride on pork chop muscle fiber type distribution, tenderness, and color characteristics1,2

Abstract: A total of 320 finishing pigs (PIC 327 × 1050; initially 98 kg) were used to determine the effects of adding Zn to diets containing ractopamine HCl (RAC) on muscle fiber type distribution, fresh chop color, and cooked meat characteristics. Dietary treatments were fed for approximately 35 d and consisted of a corn-soybean meal-based negative control (CON), a positive control diet with 10 mg/kg of RAC (RAC+), and the RAC+ diet plus 75, 150, or 225 mg/kg added Zn from either ZnO or Availa-Zn. Loins randomly selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 38 publications
1
15
2
Order By: Relevance
“…A 30-cm portion of the longissimus lumborum muscle (beginning at the 10th rib) from the left side of each pig was collected for immunohistochemical and fresh pork quality analysis. The results for the fresh pork quality analysis are reported in Paulk et al (2014).…”
Section: Methodsmentioning
confidence: 99%
“…A 30-cm portion of the longissimus lumborum muscle (beginning at the 10th rib) from the left side of each pig was collected for immunohistochemical and fresh pork quality analysis. The results for the fresh pork quality analysis are reported in Paulk et al (2014).…”
Section: Methodsmentioning
confidence: 99%
“…Studies reported RAC increased the rate of fatigue when pigs were roughly handled; however, these studies used indirect measures of blood metabolites as indicators (James et al, 2013;Peterson et al, 2015;Puls et al, 2015). Dietary RAC shifted muscle fiber type from oxidative to glycolytic metabolism (Paulk et al, 2014), but the impact of fiber shifts on fatigue remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Fibers that stained positive for both SC-71 and B-FF3 were labeled as type IIX fibers ( Fig. 1; Paulk et al, 2014). Cross-sectional area of muscle fibers was determined as the area within the dystrophin border.…”
Section: Immunohistochemistry and Histologymentioning
confidence: 99%
See 1 more Smart Citation
“…Then the cross sections were embedded in optimal cutting temperature tissue-embedding media (Fisher Scientific, Pittsburgh, PA), frozen by submersion in supercooled isopentane, and stored at −80°C until analysis. For each muscle sample, two 10-μm cryosections were collected on positively charged slides (MidSci), and muscle fibers were immunostained with antibodies validated by Town et al (2004) for the detection of primary and secondary muscle fibers and merged with the methods of Paulk et al (2014) to simultaneously identify muscle fiber cross-sectional area. Briefly, nonspecific antigen-binding sites were inhibited by incubating cryosections in 5% horse serum and 0.2% TritonX-100 (Fisher Scientific) in PBS for 30 min.…”
Section: Immunohistochemistrymentioning
confidence: 99%